A novel enterovirus and parechovirus multiplex one-step real-time PCR-validation and clinical experience - Nielsen, Alex Christian Yde (J Virol Methods, 2013)
As the number of new enteroviruses and human parechoviruses seems ever growing, the necessity for updated diagnostics is relevant. We have updated an enterovirus assay and combined it with a previously published assay for human parechovirus resulting in a multiplex one-step RT-PCR assay. The multiplex assay was validated by analysing the sensitivity and specificity of the assay compared to the respective monoplex assays, and a good concordance was found. Furthermore, the enterovirus assay was able to detect 42 reference strains from all 4 species, and an additional 9 genotypes during panel testing and routine usage. During 15 months of routine use, from October 2008 to December 2009, we received and analysed 2187 samples (stool samples, cerebrospinal fluids, blood samples, respiratory samples and autopsy samples) were tested, from 1546 patients and detected enteroviruses and parechoviruses in 171 (8%) and 66 (3%) of the samples, respectively. 180 of the positive samples could be genotyped by PCR and sequencing and the most common genotypes found were human parechovirus type 3, echovirus 9, enterovirus 71, Coxsackievirus A16, and echovirus 25. During 2009 in Denmark, both enterovirus and human parechovirus type 3 had a similar seasonal pattern with a peak during the summer and autumn. Human parechovirus type 3 was almost invariably found in children less than 4 months of age. In conclusion, a multiplex assay was developed allowing simultaneous detection of 2 viruses, which can cause similar clinical symptoms.